Ligand Assisted Thermal Atomization of Palladium Clusters: An Inspiring Approach for the Rational Design of Atomically Dispersed Metal Catalysts. (20th February 2023) - Wang, Sicong; Ding, Tao; Liu, Tong; Zhu, Yanan; Tao, Zhinan; Pang, Beibei; Liu, Xiaokang; Luo, Qiquan; Sun, Mei; Sheng, Hongting; Zhu, Manzhou; Yao, Tao
Abstract: The transformation from metal nanocluster catalysts to metal single‐atom catalysts is an important procedure in the rational design of atomically dispersed metal catalysts (ADCs). However, the conversion methods often involve high annealing temperature as well as reducing atmosphere. Herein, we reported a continuous and convenient approach to transfer Pd nanocluster into Pd single‐atom in a ligand assisted annealing procedure, by which means we reduced its activating temperature low to 400 °C. Using ex‐situ microscopy and spectroscopy, we comprehensively monitored the structural evolution of Pd species though the whole atomization process. Theoretical calculation revealed that the structural instability caused by remaining Cl ligands was the main reason for this low‐temperature transformation. The present atomization strategy and mechanistic knowledge for the conversion from cluster to atomic dispersion provides guidelines for the rational design of ADCs. Abstract : The transformation from metal nanocluster catalysts to metal single‐atom catalysts is an important procedure in the rational design of atomically dispersed metal catalysts (ADCs). Herein, an inspiring approach is reported. Cl ligands coordinated to Pd nanoclusters make them become less stable and have a stronger tendency to collapse, thus allowing the transformation from Pd nanocluster to Pd single atom to happen at a relative low temperature.